2023
DOI: 10.2147/jpr.s394321
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Empty Sella Syndrome, Fibromyalgia, and Chronic Fatigue Syndrome: The Role of Increased Cerebrospinal Fluid Pressure

Abstract: The etiopathogenesis of fibromyalgia (FM) and chronic fatigue syndrome (CFS) is not yet elucidated. Hypothalamo-pituitary-adrenal (HPA) axis dysfunction is reflected in the hormonal disturbances found in FM and CFS. Some study groups have introduced a novel hypothesis that moderate or intermittent intracranial hypertension may be involved in the etiopathogenesis of FM and CFS. In these conditions, hormonal disturbances may be caused by the mechanical effect of increased cerebrospinal fluid pressure, which hamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…In our study, we measured serum leptin, IGF-1, and IGFBP-3 levels in patients with FMS and evaluated their relationship with clinical parameters. The results of the studies which show that changes in serum IGF-1 levels play a role in FMS physiopathogenesis are inconsistent 5 , 6 , 9 , 12 , 15 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we measured serum leptin, IGF-1, and IGFBP-3 levels in patients with FMS and evaluated their relationship with clinical parameters. The results of the studies which show that changes in serum IGF-1 levels play a role in FMS physiopathogenesis are inconsistent 5 , 6 , 9 , 12 , 15 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Lack of GH secretion may also cause muscle microtrauma and/or distortion in the recovery of microtrauma in normal processes in patients at the same time. Many FMS patients have low serum GH levels, with a hypothesized etiology of dysregulated GH/IGF-I axis and in the sympathetic stress axis as well 17 , 18 . In another study, they were reported that the pituitary function was normal in fibromyalgia and the changes in the hypothalamus-GH-IGF-1 axis were largely due to hypothalamic origin and that GH cure should be recommended accordingly in future studies 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation